2018
DOI: 10.1097/md.0000000000010233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fixed orthodontic brackets on oral malodor

Abstract: Background:This systematic review and meta-analysis aimed to identify whether there is any relationship between fixed orthodontic appliances and malodor, and if self-ligating brackets (SLBs) prevent malodor better than conventional brackets (CBs).Methods:The electronic databases PubMed, Ovid, EMBASE, and the Cochrane Library were searched from inception to September 2016; a manual search was also performed. Randomized controlled and clinical controlled trials, in which experimental groups received fixed orthod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In our study, we also distinguished the appearance of these germs after 3 months of fitting the orthodontic apparatus [8]. The literature results show that Klebsiella pneumoniae and Enterobacter cloacae , which are anaerobic and do not need air or dioxygen to function, are among the major causes of halitosis [9]. Rosembloom and Tinanoff found that orthodontic treatment would result in a change in oral flora with a remarkable increase in cariogenic bacteria counts (including oral streptococci) in dental plaque and saliva [10].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also distinguished the appearance of these germs after 3 months of fitting the orthodontic apparatus [8]. The literature results show that Klebsiella pneumoniae and Enterobacter cloacae , which are anaerobic and do not need air or dioxygen to function, are among the major causes of halitosis [9]. Rosembloom and Tinanoff found that orthodontic treatment would result in a change in oral flora with a remarkable increase in cariogenic bacteria counts (including oral streptococci) in dental plaque and saliva [10].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of bias in 10 studies was low, [9][10][11]14,15,[17][18][19]21,23 while it was unclear in 6. 12,13,16,20,22,24 The methodological quality of almost all studies was positive to signaling questions in domains 1 and 4 of phase 2 of ROBIS.…”
Section: Characteristics Of Studies Included In the Reviewmentioning
confidence: 99%
“…19 2 studies measured plaque index, gingival index, bleeding on probing, and periodontal pockets but found no significant differences between selfligating and conventional brackets. 17,21 Huang et al found that oral malodors were less with self-ligating brackets. 21 No statistical differences in chairside time were observed in the study conducted by Chen et al 9 Yang et al 18 reported a shorter treatment time when using conventional bracket systems.…”
Section: Treatment Efficiency (Table 4)mentioning
confidence: 99%
See 1 more Smart Citation
“…The factors responsible for the increased development of bacterial biofilm include the application of orthodontic appliances close to the soft tissue structures, malaligned teeth, and improper oral hygiene maintenance [ 6 ]. The abundance of bacterial biofilm can lead to the development of oral health problems that include plaque-induced gingivitis, white spot lesions, and oral malodor (bad breath) [ 7 , 8 , 9 , 10 ]. The most common treatment modality used to tackle this problem addresses the repeated application of scalers (manual or ultrasonic).…”
Section: Introductionmentioning
confidence: 99%